Does the risk-taking behaviour of a group influence individual risk-taking behaviour? - Asieh Daneshi; Marcel Brass (Royal Society Open Science, 2025)
People often take more risks when in groups than when alone, but studying group-based risk-taking can be logistically challenging. This study used an online simulation of the balloon analogue risk task featuring virtual agents to examine how the presence of others influences individual decision-making. Ninety-nine participants completed 160 trials of a balloon inflation task while situated in a virtual room with five computer-generated agents. On each trial, a varying number of agents also inflated balloons and displayed either risk-taking or risk-avoiding behaviour. Results showed that participants’ risk-taking generally increased as more agents co-inflated, and this effect was stronger when the agents behaved riskily, consistent with the risky shift phenomenon. These findings demonstrate the utility of virtual simulations for exploring social influences on risk-related decisions.